1152 Prostaglandin E 1 Use In The Transfer Of Infants With Suspected Duct Dependent Congenital Heart Disease. (October 2012) - Gupta, N; Kamlin, COF; Stewart, M; Cheung, M; Patel, N
Abstract : Background: Transport of infants with suspected duct dependent congenital heart disease (DDCHD) represents a diagnostic and therapeutic dilemma, specifically in relation to use of prostaglandin E 1 (PGE1 ) to maintain ductal patency. Aims: To evaluate factors influencing, and consequences of, PGE1 use in transport of infants with suspected DDCHD or persistent pulmonary hypertension (PPHN). Methods: Retrospective study of infants' ≤10 days old with suspected DDCHD/PPHN transferred to the Royal Children's Hospital, Melbourne, by NETS (Victoria) identified from transport and hospital databases. Results: Of 142 eligible infants, 81 had DDCHD, 51 had PPHN and 10 had neither. Diagnostic accuracy of DDCHD by transport team was 77%. PGE1 was commenced in 50% of infants, 63% of DDCHD group, and 19% of non-DDCHD group. "Time critical" transfers were significantly associated with PGE1 use; transfer distance and air/land were not. PGE1 use was significantly associated with the presence of cyanosis, abnormal pulses and lower initial SpO2 and PaO2 . Ventilation and inotrope use during transfer were significantly higher in infants with DDCHD who received PGE1, than those who did not (both P 0.007). Use of PGE1 significantly shortened length of stay in PPHN but not DDCHD patients. There was no significant difference in death rates between PGE1 and no-PGE1 group. Conclusions: Although the ability of transport personnel to differentiate DDCHD from PPHN and correctly administer PGE1 was high, 35% of infants with DDCHD were transferred without PGE1 . Cyanosis, abnormal pulses and initial hypoxemia influenced the decision to start PGE1 . PGE1 may improve outcome in PPHN.